Contribution to accelerated internationalization with digital forensic accounting and metaverse circular business model innovation for Vietnam-based SMEs - Pham Quang Huy; Vu Kien Phuc (Journal of Innovation and Entrepreneurship)
Abstract This study endeavors to examine the relationship between digital forensic accounting (DFAC) and accelerated internationalization capabilities (AIC). The study posits that the relationship between DFAC and AIC is mediated by metaverse circular business model innovation (MCBMI). The data was collected from employees in small and medium enterprises (SMEs) in Vietnam employing a combination of convenience and snowball sampling approaches, utilizing a quantitative research design and deductive approach. SmartPLS version 4 software was employed to analyze the data using partial least squares-structural equation modeling. This investigation determined that AIC is insubstantially influenced by DFAC. Nevertheless, the relationship between DFAC and AIC is positively mediated by MCBMI. The findings of this investigation would function as a reliable foundation for future research endeavors, as well as for the advancement of scientific comprehension by expanding the current scope of this research line. From a practical perspective, these critical insights could facilitate the development of strategies that are specifically tailored to the implementation of circular business models, as well as policies and regulations that are pertinent to the incorporation of Metaverse platforms to enhance SMEs’ internationalization performance.